“Modo et forma”: il lessico della copia in architettura tra la fine del Medioevo e la prima età moderna - Bova, Sara (Aesthetica Preprint, 2024)
The paper aims to analyze ‘the language of the copy’, i.e. that series of locutions which, from the end of the Middle Ages to the early modern age, served as the intermediary of a mimetic relationship between the model and the novel artistic or architectural work. To this end, the study takes into particular account the terminology used in the contracts, which formally establish this link, and the various meanings of these expressions.